The impact of resistance training and collagen supplementation on joint stability and prevention of recurrent ankle sprains in amateur athletes: A Literature review - Pietrucha, Jakub; Kuna, Wojciech; Turczynowski, Kamil Igor; Turczynowski, Konrad Olaf; Gołdyn , Mateusz Józef; Łyko, Zuzanna; Rutkowska, Anna; Niski, Jakub; Studziński, Dawid (Journal of Education, Health and Sport, 2026)
Introduction: Ankle injuries are among the most common medical issues in the physically active population, accounting for nearly 15–30% of all sports-related injuries. The most frequent of these is the inversion sprain, which leads to damage of the lateral ligament complex, particularly the anterior talofibular ligament (ATFL). Although this injury is often downplayed in popular opinion, research indicates that improper treatment and a lack of rehabilitation lead to the development of chronic ankle instability (CAI) in nearly 40% of patients. Aim: The aim of this study is to review current literature regarding the role of sensorimotor training and collagen peptide supplementation in the process of strengthening ligamentous structures and improving the subjective perception of joint stability in athletes. Background: For the amateur athlete, recurrent sprains involve not only physical pain but, above all, a drastic decline in the Quality of Life (QoL), resulting from the necessity to interrupt training and increasing kinesiophobia—the fear of reinjury. Contemporary sports orthopedics is increasingly shifting away from a purely mechanical paradigm of injury treatment toward a holistic approach. The key pillars of this approach are resistance training focused on active stabilization and biochemical support through targeted collagen supplementation Review methods: A comprehensive analysis ofr esearch papers available on PubMed and GoogleScholar was conducted using keywords: